Linguistic and translational analysis of errors in translations of Mark Twain’s novel “The Adventures of Tom Sawyer” (Eurasian Journal of Philology Science and Education, 2022)
Today, there is a growing number of works of art in the world that are published and translated into various languages of the world. In this regard, the question of the correctness of the work translated by various translators and the creation of a system for determining the degree of adequacy of the translation in relation to the original text is acute. The article deals with various types of mistakes made by Russian translators when translating Mark Twain’s novel “The Adventures of Tom Sawyer”. The article aims to make a comparative analysis of 9 translations and the original text in order to determine the main types of errors made by translators and to consider the consequences of the presence of these errors in the translation. The novelty of the research is seen in the fact that these errors in the translation of the work “The Adventures of Tom Sawyer” haven’t been analyzed earlier. The method of comparative analysis of the original and translation text is used as the main method for detecting errors. The value and practical significance of this study are beyond doubt, as the analysis of mistakes made by translators will allow translators to improve the quality of the translation itself, as well as to avoid these mistakes in the future. After analyzing the translations, we can say that translators made various types of mistakes at all levels of the language and also errors related to cultural differences between the source and target language. The author of the article pays special attention to identifying distortions in the semantic content and violations of the emotional component of the work due to inadequate translation. The results of this study and recommendations will make a significant contribution to the development of the erratological aspect of translation studies.